(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The introduction of foreign genes into most of the Phoenix spp using recombinant DNA technology is not a straight forward task. In Phoenix spp application of this technology towards successful transformation proved to be a more difficult one so far no report on the successful regeneration of transgenic date palm plants has been published. We developed an efficient and reproducible variety-independent method for producing transgenic date palm (Phoenix spp) via Agrobacterium-mediated transformation. Agrobacterium rhizogenes strains LBA 9402 were used and for cotransformation experiments the strain LBA 9402 with the binary vector pBIN19 with the p35S GUS INT gene was used. Off-shoot segments from different Phoenix spp cultivars were infected with Agrobacterium rhizogenes. The development of hairy roots at a high frequency only on infected tissue pieces showed that transformation is possible. Various parameters like, effect of different genotypes on root initiation, root number and root length have been studied. Regeneration of transformed root cultures to plantlets was also attempted. Histochemical GUS assay and polymerase chain reaction analysis of hairy roots confirmed the presence of GUS gene. Agrobacterium tumifaciensmediated transformation was also performed using the leaves of off-shoot explants. Agrobacterium tumefaciens strains: I) GV3101 with the vir plasmid pMP90 the strain C58C1 ATHV with the vir-plasmid pTiBo542 (=pEHA101; Hood et al. 1986) was used. The nptII gene (neomycin phosphotransferase) was used as a selectable marker gene. The ?-Glucuronidase-gene (GUS-Gene: Jefferson et al. 1987) under control of the Ubi- and 35S-Promotors, with an Intron (Vancanneyt et al. 1990), was used as the reporter gene. We also used the genetically engineered Agrobacterium tumefaciens strain LBA4404 as a vector for infection in the transformation experiment, which contains plasmid pBI121 of 14 KDa (binary vector). This binary vector contains following genes within the right border (RB) and left border (LB) region of the construct: The udiA gene (Jefferson, 1986) predetermining GUS (?-glucuronidase), driven by CaMV promoter and NOS terminator. This reporter gene can be used to assess the efficiency of transformation. The nptII gene (Herrera-Estrella et al., 1983) encoding neomycin phosphotransferase II (nptII) conferring kanamycin resistance, driven by NOS promoter and NOS terminator. The bacterium also contains plasmid pAL4404 which is a disarmed Ti plasmid (132 KDa) containing the virulence genes. For the confirmation of transgenes, calli were taken from the growing callus mass for DNA isolation. PCR- and Southern analysis was performed to determine the integration and the copy number of the transgene. The GUS-test was performed to demonstrate ß-glucuronidase expression. The transgenic plantlets were kept in a hardening room for four weeks and they will be transferred to a growth chamber with controlled environment for further establishment. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19841 J. Bangladesh Agril. Univ. 11(2): 171-176, 2013